KAPE PAGI Flashcard-based Programme Improves Patient Knowledge after Tooth Extraction at Galis Community Health Centre - Itafiqoh Sjukur; Hasinuddin Hasinuddin; Suhron Suhron (CV. AFDIFAL MAJU BERKAH, 2026)
Tooth extraction is a common procedure in primary care and has the potential to cause post-operative complications if patients do not understand the aftercare instructions properly. Standardised and easy-to-understand educational media are needed to reinforce patients' knowledge of post-extraction care. This study aimed to assess the improvement in patients' knowledge after tooth extraction following education using KAPE PAGI flashcards at the Galis Community Health Centre, Bangkalan Regency. The study used a pre-experimental one-group pretest–posttest design on 24 patients after tooth extraction. Knowledge was measured using a questionnaire before the intervention (pretest) and after the provision of education (posttest). Data were analysed descriptively and the pretest–posttest difference was tested using a paired t-test with a significance level of 0.05. The results showed that the mean knowledge score increased from 62.1 ± 12.0 on the pretest to 80.2 ± 10.1 on the posttest, with a difference of 18.1 ± 15.0 points. The paired t-test showed a significant difference (t(23)=5.91; p<0.001) with a large effect size (d=1.21). These findings indicate that education using KAPE PAGI-based flashcards is associated with an increase in patient knowledge after tooth extraction in a primary care setting. The integration of flashcards into the post-procedure education SOP, as well as training and monitoring of implementation, is recommended. Further research with a control group and follow-up on knowledge retention is needed to strengthen the evidence.